O sistema moderno/colonial de gênero em processos de securitização: disputas discursivas na Bolívia (2011/2019) - Marques, Renata Rodrigues (2022)
This dissertation discusses the relationship between social classifications and securitization. Processes of decolonization, racialization and gendering are considered in certain politicalideological contexts. The theoretical reflection is situated within the scope of studies on securitization and its new approaches, followed by an empirical analysis of political confrontation in Bolivia, in the years 2011 and 2019. Bolivia has gone through a process of state change, defined as plurinational since the 2009 constitution. However, in circumstances of political confrontation, ruling elites continued to use the security forces to suppress social protests, which makes securitization processes explicit as instruments of government. It starts with the following research problem: How does social classification, mainly in terms of gender and racialization, interfere in securitization processes that start from different politicalideological conjunctures? The concept of the Modern/Colonial Gender System is used to emphasize a perspective rooted in structural and historical processes as definers of social classification, mainly in terms of 'race' and gender. Qualitative research is carried out, adopting reflexive and explanatory elements, understanding social classification and securitization processes as associative variables. Therefore, the general objective is to understand how social classifications are configured in the securitization dynamics of the selected cases. To fulfill these objectives, the methodological construction of this dissertation dialogues with a proposal of multimethods, focused not only on the contextualization of empirical research, but also on the mapping of securitizing discourses and its respective sets of social representations. Thus, two case studies are carried out examining particular situations, followed by content analysis using the IRAMUTEQ software. The collected material is divided into three categories: political speeches, narrative speeches and media speeches. As a last process, critical discourse analysis is employed to perceive the main discursive disputes. Comparative research tools are used to assess the different securitization processes, embracing different ideological conjunctures. The data demonstrate different perceptions regarding securitization movements and audience acceptance. The securitization in the first case is mostly practical, while the second case finds more discursive evidence. Dimensions of gender and racialization are found in both cases, however, in relation to the direct effects of (in)securitization, the intensity of use of coercive instruments and the success of securitization predominate in the second case.